The Impact of Sexual Media on Second Language Vocabulary Retrieval - Çetin, Yakup (Journal of religion and health, 2015)
Both Islam and Christianity warn their adherents not to view or to display obscene matter. Aside from religious consequences in the afterlife for such behavior, this study was conducted to determine if viewing sexual media has a detrimental effect in earthly life. Adolescents (n = 64) 17-22 years were exposed to two types of visual stimuli containing sexual or neutral content for 30 min. The participants, seated in rooms with comfortable chairs and provided with snacks, were shown a selection of 18 German words via a PowerPoint slideshow, which included a picture, an audio recording, and the written form of each word. The experimental group, which was exposed to arousing visual stimuli with mild sexual content (movie trailers, music video clips, and TV commercials), remembered significantly fewer words than the control group, which viewed a nature documentary without sexual content. T-test scores revealed that exposure to sexually arousing media impaired memory for second language (L2) vocabulary. Apart from leading to dire consequences in the hereafter, the results of the study demonstrate that viewing obscene material also causes harm in this life.